Adoption of LGBT‐friendly practices: The effect of institutional pressures and strategic choice. (30th August 2019) - Roumpi, Dorothea; Giannakis, Panagiotis; Delery, John E.
Abstract: This study explores contextual and organisational factors that influence the likelihood of adopting lesbian, gay, bisexual, and transgender (LGBT)‐friendly practices. Drawing on institutional theory, we hypothesise that state laws, state conservativism, and localised LGBT‐friendliness density will have a direct effect on the adoption of LGBT‐friendly practices. Given the observed variation in the adoption of these practices, we also draw on strategic choice and the upper echelons perspective and hypothesise that the effect of institutional mechanisms is moderated by the beliefs and values of powerful organisational agents (chief executive officers and boards of directors). Our sample consists of 201 U.S.‐based Fortune 1000 companies over a period of seven years, and we test our hypotheses using a Cox proportional hazards survival analysis. Our results offer support for the role of state conservativism and localised LGBT‐friendliness density in the likelihood of LGBT‐friendly practices adoption, as well as for the moderating role of chief executive officer and board of directors' political orientation.